ANALYSIS OF TICKS OF IXODES PERSULCATUS И DERMACENTOR RETICULATUS SPECIES WITH TRANSMISSIBLE DISEASES IN KIROV REGION - S. A. Volkov (Sankt-Peterburg : NIIÈM imeni Pastera, 2016)
Borreliosis, encephalitis, anaplasmosis, ehrlichiosis and babesiosis belongs to tick-borne transmissive diseases. These diseases are dangerous for human and animals as well. Moreover, some animals can have no clinical signs of these diseases. These diseases are widely spread across Russian Federation, although only encephalitis and borreliosis (Lyme disease) are being monitored nowadays. At the same time anaplasmosis, ehrlichiosis and babesiosis (pyroplasmosis) are not being monitored. Thus a goal of monitoring of these diseases appears. The main vector for these diseases are ticks. Ticks can carry and transmit causative agents of the diseases to domestic and wild animals. Thus a goal of monitoring transmissible diseases in different population of ticks gathered in our country appears. In this study PCR was chose. This method is perspective and is widely used to detect infectious diseases nowadays. Moreover this method allows getting results in quite short period of time. The goal of this work is to determine the presence of causative agents of tick-borne diseases in ticks of different species gathered in different areas of Kirov region in 2010–2015 with the help of PCR. Moreover the goal was to determine if there is a relation between a number of infected ticks and its species. To solve these goal a primers, PCR conditions, method of extraction of total nucleic acid from fixed and alive ticks were engineered. Method of extraction of total nucleic acids allowed with the help of a reverse transcriptase to determine tick-borne encephalitis virus in samples. Analyzed ticks were gathered in Kirov region. It was determined that main vectors in these region are of an Ixodes persulcatus and a Dermacentor reticulatus species. It was prooved that the number of infected ticks can vary in time. It was also proved that there is no significant difference in the number of infected with TBEV and Lyme disease causative agents but there is a significant difference in the number of infected ticks with anaplasmosis, ehrlichiosis and babesiosis causative agents.